2019
DOI: 10.1113/jp278920
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term bed rest‐induced insulin resistance cannot be explained by increased mitochondrial H2O2 emission

Abstract: Key pointsr We determined if bed rest increased mitochondrially derived reactive oxygen species and cellular redox stress, contributing to the induction of insulin resistance.r Bed rest decreased maximal and submaximal ADP-stimulated mitochondrial respiration. r Bed rest did not alter mitochondrial H 2 O 2 emission in the presence of ADP concentrations indicative of resting muscle, the ratio of H 2 O 2 emission to mitochondrial O 2 consumption or markers of oxidative stress r The present data suggest strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 51 publications
9
50
2
Order By: Relevance
“…It is duly noted that this study was conducted on healthy, young male adults, and further studies need to be conducted in order to confirm whether the previously discussed phenotype would persist in other patient populations that are confined to a hospital or other medical facility for extended periods of time. (Dirks et al 2020). Although the present investigators found that the mechanisms underlying bed rest-induced IR did not match previous findings with high-fat diet-induced IR, the study steers future research in a direction where the mechanism underlying bed rest-induced IR may be determined.…”
Section: Journal Clubcontrasting
confidence: 91%
See 3 more Smart Citations
“…It is duly noted that this study was conducted on healthy, young male adults, and further studies need to be conducted in order to confirm whether the previously discussed phenotype would persist in other patient populations that are confined to a hospital or other medical facility for extended periods of time. (Dirks et al 2020). Although the present investigators found that the mechanisms underlying bed rest-induced IR did not match previous findings with high-fat diet-induced IR, the study steers future research in a direction where the mechanism underlying bed rest-induced IR may be determined.…”
Section: Journal Clubcontrasting
confidence: 91%
“…Furthermore, markers of oxidative stress (4-hydroxynonenal and reduced/oxidized glutathione levels) did not change following bed rest. This accords with the lack of an increase in ROS production measured by H 2 O 2 emission levels (Dirks et al 2020).…”
Section: Bed Rest-induced Ir Not Caused By Increased H 2 O 2 Emissionsupporting
confidence: 88%
See 2 more Smart Citations
“…Some values were excluded from the analysis due to technical errors, therefore final analysis was conducted on n = 7-8 per group. [32] we also reported total ETS subunit protein content.…”
Section: Ex Vivo Glucose Uptakementioning
confidence: 99%